(untitled) (KIUT Publication, 2025)
This article explores innovative energy-efficient architectural solutions in the city of Samarkand. It focuses on bioclimatic design principles, passive technologies, the use of renewable energy sources, smart HVAC systems, and digital simulation of building energy performance. The article discusses both the architectural and engineering aspects of modern sustainable buildings, while preserving cultural identity. Case studies of public and educational buildings are analyzed.